The usage of phenotyping, genetics and functional genomics approaches to improve environmental stress factors in banana - Carpentier, Sebastien C.; Eyland, David (Burleigh Dodds Science Publishing Limited, 2020)
In an agricultural approach, an abiotic ‘stress’ is a disadvantageous influence coming from the environment threatening yield. Hence, growers focus on reducing abiotic stress to safeguard their production and profit. Plant growth is determined by the interaction of the genotype with the environment, while crop growth is determined by the interaction of the genotype with the environment and the farm management (G×E×M). Absolute classifications of genotypes towards tolerance are therefore not possible. The terms ‘susceptible’ and ‘tolerant’ are relative terms which depend on the given set of genotypes evaluated under a given set of environmental conditions. Ideally, all genotypes need to be screened in the field for at least two crop cycles and within the area of interest. However, screening numerous banana genotypes from start to harvest would be extremely labour, time and cost-intensive. Therefore, a workflow is required where the existing biodiversity is first screened through an early screening process in a controlled environment, especially if a link is to be made to molecular analysis. A controlled setup ensures a known and acceptable variability in soil water potential, vapour pressure deficit (VPD) and light. The focus of early screening is high throughput, which means the screening of many plants/genotypes as thorough as possible within a limited time. The more variation that can be attributed to a difference in genetic makeup without being overshadowed by noise due to the environment, the more precise the differential reactions between genotypes can be distinguished. Therefore, the difference between genotypes can be detected much more accurately in a controlled setup, while the time needed for screening is reduced. To be relevant for banana breeding, we need efficient variables that are a good proxy for yield in the specified target region of interest and that can be correlated to genetic markers.